CHARACTERISTICS OF TERMS CONCERNING THE CONSTRUCTION OF BUILDINGS (Scientific journal of the Fergana State University, 2024)
This article focuses on studies in the field of terminology, scientific views of scientists. At the same time, the difficulties in the translation of terms related to buildings and structures are highlighted, and solutions are shown with the help of concrete examples.